Derivation of Hemispheric Ionospheric Current Functions From Ground‐Level Magnetic Fields. Issue 4 (16th April 2019) - Weimer, D. R.
Abstract: The horizontal currents in the high‐latitude ionosphere are the primary driver of the magnetic field perturbations that are observed at the surface of the Earth. These currents and their ground effects are an important aspect of the magnetosphere‐ionosphere coupling process. This paper discusses the method of inversion that uses spherical harmonic potential function, in which magnetic field measurements on the ground can be used to derive maps of the "ionospheric equivalent currents, " a mathematical representation of the horizontal currents flowing on a thin shell. It is shown that the use of both internal telluric and external current sources is required when fitting the spherical harmonic series; otherwise, the ionospheric currents will be overestimated. Furthermore, the inversion needs to compensate for magnetic effects of the magnetospheric ring current; otherwise, this current is projected onto the ionosphere. The amplification of the surface horizontal magnetic field and the suppression of the vertical magnetic field are demonstrated. The equivalent currents may be useful for estimating the ionospheric conductivity values. Additionally, these currents can be compared with the results from simulation models as a means of validation. Plain Language Summary: Currents in the high‐latitude ionosphere produce changes in the magnetic field at the surface of the Earth. This paper discusses a technique that uses measurements of these changes in the magnetic field to solve the problem of deriving maps of the currents flowing in the ionosphere. While the first description of this method dates back to the 1940s, this obscure practice can now be more useful with the more recent availability of globally distributed magnetic field measurements. The details of this particular "inversion" technique are described. It is shown that for greatest accuracy, the mirror image currents that occur beneath the Earth's surface need to be considered, as well as the currents that are actually located in the magnetosphere, far above the ionosphere. This result is useful in the study of the interaction between the solar wind and the Earth's magnetosphere, and the resulting currents. Key Points: Calculations of ionospheric equivalent current functions from ground‐level magnetic field values are reviewed The vertical magnetic field is needed to derive the telluric currents, and effects of the ring current should be considered The telluric currents enhance the horizontal field and suppress the vertical component